Relación del estado nutricional y la dieta de los adultos mayores de la casa hogar Betania año 2015 - Gañay Agurto, Karina Doris (2016)
Nutrition in elderly plays a very important role as an adequate intake of essential nutrients in this age ensures a better nutritional health status. This research was aimed to determine the relationship of diet and nutritional status of adults at the “Casa Hogar” called Betania during 2015. The methodology used was transversal, prospective, observational and bibliographic. The study was developed in “Casa Hogar” Betania with a sample of 34 elderly. The technique was used with the observation guide; instrument which the following results were established. 58.82% are men in an age over 85. And the 47.06% of these are mestiza race. Similarly, 91.18 belong to mixed ethnicity and 50% of them are widowed. 61.76% of them have primary schooling and likewise, 73.53% do not receive incomes. On the other hand, 82.35% receive the general diet hiccups sodium. By the chi square test it was determined the correlation between nutritional status and diet. 0n the other hand, the level of knowledge by means of the staffs who work in cooking department100% of them have an average knowledge about the diet that the elderly have to follow. To improve the nutritional status of older adults, educational talks were provided to administrative as well as kitchen staff assistants. Besides, a triptych with educational material was provided to the engaged people. In addition, an action plan was involved which included relaxation therapies, hiking, active and passive exercises. In other words the researcher supported the people about the caring about elderly, also gave some information and helped do some menus to improve the nutritional status of the refugees ran. Finally, it will be modest to mention that an inadequate nutrition in adulthood may cause health problems and thus reduce life expectancy.